Religious freedom and the marginalization of religion in the public sphere - Sztajer, Sławomir (Polskie Towarzystwo Religioznawcze, 2014)
Modern liberal democracy contains an internal contradiction concerning the presence of religion in the public sphere. On one hand, liberal democracy guarantees a religious freedom on the basis of which individuals may choose, abandon, change, publicly profess and spread their own religion. On the other hand, the structural and functional changes that take place in modern societies and the accompanying changes in consciousness result in restricting religious freedom to a specific area that hasbeen defined from outside. In modern societies, there are in reality mechanisms of the marginalization of religion which make it difficult to exercise such basic human rights as religious freedom. The marginalization of religion takes place through the decomposition and transformation (semantic and functional) of religious messages. Due to these mechanisms, the attempts to include religious contents in the public discourse are associated with a significant risk of distorting them, taking them out of context, and transforming them in the framework of nonreligious meaning systems.
Keywords: religious freedom; marginalization of religion; mechanisms of marginalization of religion; secularity principle